Suberites lutkenii Morozov, Strelkova, Zimina & Sabirov, 2023, s. lat. ... - Morozov, Grigori; Strelkova, Natalya Anisimova; Zimina, Olga; Sabirov, Rushan (Zenodo, 2023)
Suberites lutkenii s. lat. Schmidt 1870 Suberites lütkenii: Schmidt 1870, p. 47, Pl. V, fig. 7; Marenzeller 1886, pp. 11–12; Topsent 1913, pp. 25–26; Hentschel 1929, p. 872; Burton 1934, p. 14; Alander 1942, p.79; Laubenfels 1953, pp. 12–13, fig.7. Suberites montalbidus: Carter 1880, p. 256; Carter 1882, p. 353; Fristedt 1885, pp. 19–20, Pl. 2, figs. 4a–e; Fristedt 1887, pp. 428–429; Levinsen 1893, pp. 413–414, fig. 23; Lambe 1894, pp. 127–128, pl. III, fig. 6a–c; Lambe 1900, pp. 24–25; Swartschewsky 1906, p. 318 –319, pl. XIII, fig. 3; Morozov et al. 2019, pp. 2973–2975, fig. 8a–h; Suberites spec.: Vosmaer 1882, pp. 32–33; pl. I, figs 22–23; pl. IV, figs 140–144. Suberites domuncula ficus: Koltun 1959, p. 95, figs 66–67; pl. XXXIV, figs 1–3; pl. XXXVI, figs 1–2. Suberites lutkenii Schmidt 1870 is another example of a taxonomically problematic species. Schmidt described a fig-shaped S. lutkenii from the North Sea and East Greenland. According to Schmidt (1870), the choanosomal skeleton of this sponge ... : Published as part of Morozov, Grigori, Strelkova, Natalya Anisimova, Zimina, Olga & Sabirov, Rushan, 2023, A preliminary account of the Arctic / Subarctic Suberites (Porifera: Demospongiae) fauna, pp. 50-70 in Zootaxa 5357 (1) on pages 52-53, DOI: 10.11646/zootaxa.5357.1.2, http://zenodo.org/record/10012504 ...